ANALISIS PROSES BERPIKIR KRITIS SISWA DALAM PEMECAHAN MASALAH MATEMATIKA PADA POKOK BAHASAN POLA DAN BARISAN BILANGAN - Romanti Ester Noel; Ryan Nizar Zulfikar; Nia Kurniaty Rukman (MEGA: Jurnal Pendidikan Matematika, 2022)
This study aims to analyze how students’ critical thingking processes in solving mathematical problems on the subject of patterms and sequences of numbers of students at SMP N 3 Fatuleu Tengah Satap. This study used a qualitative descriptive approach. Class VIII at SMP N 3 Fatuleu Tengah Satap, in solving patern and number sequence material questions the instrument provided in this study were 1) Critical Thingking test sheets, 2) Interviews, 3) Documentation. Documentation data analysis in this study,namely, 1) Data reducation, 2) presentation of data, 3) drawing conclusion/verivication based on data analysis, it can be concluded that 3 students with high mathematical abilities can go thourgh 4indicators and stages of the critical thingking process consisting of clarification (understand the problem), analysis (analysis the problem). Completion strategies (solving problems), and inference (making conclusions) on medium mathematical abilities students only go through the clarification and analysis stages but do not fulfill the strategy and inference stages and students with low mathematical abilities, namely students who interprect critical thingking on the answer sheet but are incomplete in answering.